Impact of Two Medicaid Prior-Authorization Policies on Antihypertensive Use and Costs Among Michigan and Indiana Residents Dually Enrolled in Medicaid and Medicare: Results of a Longitudinal, Population-Based Study - Law, Michael R. (2010)
BACKGROUND: In response to rising pharmaceutical costs, many state Medicaid programs have implemented policies requiring prior authorization for high-cost medications, even for established users. However, little is known about the impact of these policies on the use of antihypertensive medicines in the United States. OBJECTIVE: The aim of this longitudinal, population-based study was to assess comprehensive prior-authorization programs for antihypertensives on drug use and costs in a vulnerable Medicaid population in Michigan and Indiana. METHODS: A prior-authorization policy for anti-hypertensives was implemented in Michigan in March 2002 and in Indiana in September 2002; Indiana also implemented an antihypertensive stepwise-therapy requirement in July 2003. Our study cohort included individuals aged ≥18 years in Michigan and Indiana who were continuously enrolled in both Medicaid and Medicare from July 2000 through September 2003. Claims data were obtained from the Centers for Medicare and Medicaid Services. We included all antihypertensive medications, including diuretics, angiotensin-converting enzyme inhibitors, calcium channel blockers, β-blockers, α-blockers, and angiotensin II receptor blockers. We used interrupted time-series analysis to study policy-related changes in the total number and cost of anti-hypertensive prescriptions. RESULTS: Overall, 38,684 enrollees in Michigan and 29,463 in Indiana met our inclusion criteria. Slightly more than half of our cohort in both states was female (53.29% in Michigan and 56.32% in Indiana). In Michigan, 20.23% of patients were aged ≥65 years; 77.44% were white, 20.11% were black, and the remainder were Hispanic, Native American, Asian, or of other or unknown race. In Indiana, 20.07% were aged ≥65 years; 84.93% were white, 13.64% were black, and the remainder were Hispanic, Native American, Asian, or of other or unknown race. The implementation of both policies was associated with large and immediate reductions in the use of nonpreferred medications: 83.33% reduction in the use of such drugs in Michigan (−84.30 prescriptions per 1000 enrollees per month; P < 0.001) and 35.76% in Indiana (−64.45 prescriptions per 1000 enrollees per month; P < 0.001). As expected, use of preferred medications also increased substantially in both states (P < 0.001). Overall, antihypertensive therapy immediately dropped 0.16% in Michigan (P = 0.04) and 1.82% in Indiana (P = 0.02). Implementation of the policies was also associated with reductions in pharmacy reimbursement of $616,572.43 in Michigan and $868,265.97 in Indiana in the first postpolicy year. CONCLUSIONS: Prior authorization was associated with lower use of nonpreferred antihypertensive drugs that was largely offset by increases in the use of preferred drugs. The possible clinical consequences of policy-induced drug switching for individual patients remain unknown because the present study did not include access to medical record data. Further research is needed to establish whether large-scale switches in medicines following the inception of prior-authorization policies have any long-term health effects.